Catchment zoning for freshwater conservation: refining plans to enhance action on the ground. Issue 4 (18th June 2015) - Hermoso, Virgilio; Cattarino, Lorenzo; Kennard, Mark J.; Watts, Mathew; Linke, Simon; Mac Nally, Ralph
Summary Recent advances in freshwater conservation planning allow addressing some of the specific needs of these systems. These include spatial connectivity or propagation of threats along stream networks, essential to ensure the maintenance of ecosystem processes and the biodiversity they sustain. However, these peculiarities make conservation recommendations difficult to implement as they often require considering large areas that cannot be managed under conventional conservation schemes (e.g. strict protection). To facilitate the implementation of conservation in freshwater systems, a multizoning approach with different management zones subject to different management regimes was proposed. So far, this approach has only been used in post hoc exercises where zones were allocated using expert criteria. This might undermine the cost‐effectiveness of conservation recommendations, because both the allocation and extent of these zones have never been optimized using the principles of systematic planning. Here, we demonstrate how to create a catchment multizone plan by using a commonly applied tool in marine and terrestrial realms. We first test the capability of Marxan with Zones to address problems in rivers by using a simulated example and then apply the findings to a real case in the Daly River catchment, northern Australia. We also demonstrate how to address common conservation planning issues, such as accounting for threats or species‐specific connectivity needs in this multizone framework, and evaluate their effects on the spatial distribution and extent of different zones. We found that by prioritizing the allocation of zones subject to different management regimes, we could minimize the total area in need of strict conservation by a twofold factor. This reduction can be further reduced (threefold) when considering species' connectivity needs. The integration of threats helped reduce the average threats of areas selected by a twofold factor. Synthesis and applications. Catchment zoning can help refine conservation recommendations and enhance cost‐effectiveness by prescribing different management regimes informed by ecological needs or distribution of threats. Reliable information on these factors is a key to ensure soundness of planning. Freely available software can be used to implement the approach we demonstrate here.